058 THE ROLE OF FEMALE SEX IN THE CONTEMPORARY TREATMENT OF THE LEFT MAIN CORONARY ARTERY INSIGHTS FROM THE W-DELTA (WOMEN-DRUG ELUTING STENT FOR LEFT MAIN CORONARY ARTERY DISEASE) REGISTRY. (24th May 2013) - Buchanan, G L; Chieffo, A; Meliga, E; Mehran, R; Park, S J; Onuma, Y; Capranzano, P; Valgimigli, M; Jegere, S; Makkar, R; Palacios, I F; Kim, Y H; et al.
Abstract : Background: The optimal revascularization strategy of women with unprotected left main coronary artery (ULMCA) disease is unknown. Therefore, the aim of this study was to evaluate long-term clinical outcomes in this cohort treated with percutaneous coronary intervention (PCI) utilising drug-eluting stents (DES) versus coronary artery bypass grafting (CABG). Methods: All consecutive women from the Drug Eluting stent for LefT main coronary Artery disease (DELTA) Registry with ULMCA disease treated by PCI with DES or CABG were analysed. A propensity matching was performed to adjust for baseline differences between the 2 treatment groups. Results: In total, 818 women were included: 489 (59.8%) underwent treatment with PCI with DES versus 329 (40.2%) with CABG. Propensity score matching identified 176 matched pairs of patients, with no differences in the primary study objective of death, myocardial infarction (MI) or cerebrovascular accident (CVA) HR 0.711; 95% CI 0.387 to 1.308; p=0.273), all-cause (HR 0.722; 95% CI 0.357 to 1.461; p=0.365) or cardiovascular mortality (HR 1.100; 95% CI 0.455 to 2.660; p=0.832), MI (HR 0.362; 95% CI 0.094 to 1.388) or CVA (HR 1.200; 95% CI 0.359 to 4.007; p=0.767). However, there was an advantage of CABG over PCI in major adverse cardiovascular and cerebrovascular events (MACCE) (HR 0.429; 95% CI 0.254 to 0.723; p=0.001), driven exclusively by target vessel revascularization (TVR) (HR 0.185; 95% CI 0.079 to 0.432; p<0.001). Conclusions: In women with significant ULMCA disease, no difference was observed in death, MI and stroke at long term follow-up. However, repeat revascularization remained higher in the PCI cohort.